Techno-Economic Analysis of Hybrid Diesel Generators and Renewable Energy for a Remote Island in the Indian Ocean Using HOMER Pro - Riayatsyah T.M.I.; Geumpana T.A.; Fattah I.M.R.; Mahlia T.M.I. (MDPI, 2023)
alternative energy; Indian Ocean; Indonesia